PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS ASESMEN PORTOFOLIO TERHADAP HASIL BELAJAR SISWA PADA MATERI KOLOID - yudhi setiawan; lisa utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
The  present  study  was  encouraged  by  the  low  learning  outcomes  of  students  at  MAN  1  Pekanbaru that  were  influenced  by  the  lack  of  students’  participation  during  learning  process  and  caused teacher-centered  learning.  This  study  was  a  quasi-experimental  research  with  Pretest-Posttest Control  Group  design.  It  aimed  at  investigating the  effect  of  implementing  learning  model  “Guided Inquiry-Based  Portfolio  Assessment”  on  students’  chemistry  learning  outcomes  in  colloid  topic  at XI  Grade  of  State  Islamic  Senior  High  School  1  Pekanbaru.  Afterwards,  the  samples  of  this  study were  students  of  XI  Science  2  class  as  an  experimental  class  and  XI  Science  3  as  a  control  class taken  through  simple  random  sampling  from  all  students  of  XI  Science  classes  in  academic  year 2015/2016  as  population.  In  addition,  the  data  was  collected  by  using  tests  including  homogeneity test  as  the  preliminary  data  in  the  previous  materials  and  pretests  and  posttests  as  the  last  data, documentation,  and  observation.  Then,  the  data  were  analyzed  by  using  t-test.  As  the  result,  it  was obtained  that  tobtained  =2.880  and  ttable  =2.000  in  significance  level  5%.  Therefore,  it  showed  that tobtained  ≥  ttable  so  that  Ho  was  rejected  and  Ha  was  accepted  which  indicated  that  there  was  an  effect of  implementing  learning  model  “Guided  Inquiry-Based  Portfolio  Assessment”  on  students’ chemistry  learning  outcomes  in  colloid  topic  at  XI  Grade  of  State  Islamic  Senior  High  School  1 Pekanbaru with  influence  coefficient  12.5%. Key  words: 1. learning  model  “Guided  Inquiry-Based  Portfolio  Assessment”,  learning  outcomes, colloid.